Critique of fourier transform infrared microspectroscopy applications to prostate pathology diagnosis - Aning, Jonathan (Cranfield University, 2010)
Prostate cancer is a biologically heterogenous disease with considerable variation in clinical aggressiveness. Gleason grade, the universally accepted method for classification of prostate cancer, is subjective and gives limited predictive information regarding prostate cancer progression. There is a clinical need for an objective, reliable tool to help pathologists improve current prostate tissue analysis methods and better assess the malignant potential of prostate tumours. Fourier Transform Infrared (FTIR) microspectroscopy is a powerful bioanalytical technique that uses infrared light to interrogate biological tissue. The studies detailed in this thesis examine the ability of FTIR combined with multivariate analysis to discriminate between benign, premalignant and malignant prostate pathology in snap frozen, paraffinated and deparaffinated tissue. Prostate tissue was collected during and after urological procedures performed between 2005 and 2008. The tissue was analysed utilising a bench top FTIR system in point and image mapping modes. The histology under interrogation was identified by a uro- pathologist. Multivariate analysis was applied to the spectral dataset obtained. FTIR performance was evaluated. FTIR was able to reproducibly discriminate between benign and malignant prostate tissue in a pilot study. Cross validated diagnostic algorithms, constructed from the spectral dataset in this experiment, achieved sensitivities and specificities of 95% and 89% respectively. FTIR analysis of transverse paraffinated and deparaffinated radical prostatectomy sections achieved good differentiation of the benign, premalignant and malignant pathology groups. However the performance of diagnostic algorithms constructed from this dataset under cross validation was poor. The work in this thesis illustrates the potential of FTIR to provide an objective method to assist the pathologist in the assessment of prostate samples. The limitations of the technique and directions for future work are presented.